Hubungan Status Gizi, Siklus Menstruasi, dan Lama Menstruasi Dengan Kejadian Anemia pada Remaja Putri Usia 15-16 Tahun di SMA Pembina Palembang Tahun 2022 - Intan Permata Sari; Ahmad Arif; Helni Anggraini (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
Anemia is caused by a lack of iron in the body. Iron deficiency itself can be caused by several things, such as low iron food intake or maybe iron in maakanan is found in a form that is difficult to absorb, normal anemia<12mg/dl.The purpose of this study is to determine the relationship between the nutritional status of the menstrual cycle and the length of menstruation with the incidence of anemia in young women aged 15-16 years at Pembina Palembang High School in 2022. The population in this study was all young women in the 2021-2022 school year with 134 respondents. The sample to be studied must meet the inclusion and exclusion criteria of 56 respondents and the total sampling technique. There were 32 respondents (57.1%) of young women who experienced anemia, and 24 respondents (42.9%) And from the chi-square trial between the variables of nutritional status, menstrual cycle, and menstrual duration with the incidence of anemia in adolescent girls aged 15-16 years, the results of this study showed that from 56 respondents, 32 respondents (57.1%) had abnormal nutritional status of 29 respondents (51.8%) while the menstrual cycle was abnormal, respondents were 31 respondents (55.4%), and abnormal menstrual duration 34 (60.7). From the statistics of the Chi-Square test that compares pvalue with the level of meaningfulness of α = 0.05, it shows that there is a meaningful relationship between nutritional status and adolescent anemia p value (0.001), menstrual cycle p value (0.009), and menstrual length p value (0.005). Thus there is a meaningful correlation in a sympathetic manner and between Nutritional Status, Menstrual Cycle, Duration of Menstruation with the incidence of anemia in young women aged 15-16.The results of this study are expected to be used as inputs for improving the quality of health in young women aged 15-16 so that it can reduce the incidence of anemia at Pembina Palembang High School.